2005
DOI: 10.1177/000331970505600514
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Valve Perforation by Permanent Pacemaker Lead

Abstract: Tricuspid valve perforation with pacemaker lead is one of the extremely rare complications of transvenous pacemaker implantation. Approximately all reported cases have been diagnosed at autopsy. The authors present a case of tricuspid valve perforation caused by pacemaker lead that was diagnosed during cardiac surgery and treated successfully by removing the lead and suturing the tricuspid valve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…There have been few case reports of PPL-related TR published in the literature [5][6][7][8] showing that this pathology is due to various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few case reports of PPL-related TR published in the literature [5][6][7][8] showing that this pathology is due to various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of severe TR was due to leaflet malcoaptation and they hypothesised that the AV surgery was responsible for the conformational changes between cardiac chambers, TV and the PPLs, causing severe TR. The other mechanisms reported are either immobilisation or perforation of the anterior tricuspid leaflet or entrapment of the lead shaft in the fused septal and posterior tricuspid leaflets [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…One pilot study (18) showed improved symptoms and ventricular function when biventricular pacing was instituted in patients with presumed RV pacing-induced LV failure. In addition, case reports suggest that rightsided pacemaker wires may entrap or perforate the tricuspid valve, presenting with severe insufficiency (or even stenosis) and isolated RHF (19,20). Tricuspid insufficiency may also occur following RV biopsy, presumably as a result of damage to the chordae and loss of tricuspid valve coaptation (21).…”
Section: What Is It?mentioning
confidence: 99%
“…TV perforation after lead implantation can result in TV regurgitation . In case reports published on lead‐related TV perforations, the time period in which patients present with symptoms after implantation is from four months to 14 years (Table ) . The unique characteristic of our case is that the diagnosis of perforation was only two weeks after implantation.…”
Section: Discussionmentioning
confidence: 81%
“…Passage of endocardial leads through the TV can perforate a leaflet, leading to severe TV injury, and regurgitation . In the literature, patients present with symptoms of TV regurgitation from leaflet perforation four months to 14 years after PPM or ICD implantation (Table ) . We present a case of acute severe TV regurgitation due to perforation of the septal leaflet two weeks after ICD implantation and review the literature associated with this complication.…”
Section: Case Reports Of Tricuspid Valve Leaflet Perforation By a Ppmmentioning
confidence: 97%